2011
DOI: 10.1089/acm.2009.0673
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Osteopathic Manipulative Treatment of Female Patients with Migraine: Results of a Randomized Controlled Trial

Abstract: This study affirms the effects of OMT on migraine headache in regard to decreased pain intensity and the reduction of number of days with migraine as well as working disability, and partly on improvement of HRQoL. Future studies with a larger sample size should reproduce the results with a control group receiving placebo treatment in a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 23 publications
3
74
0
6
Order By: Relevance
“…These positive outcomes were less evident in two studies: the double-blind, randomised placebo-controlled study on levetiracetam in CDH by Beran and Spira [6] and the randomized study on osteopathic manipulative treatment of female patients with migraine by Voigt et al [16], In these reports, however, some changes towards improvement in QoL and in disability were observed. Similar results were found in the two observational studies by Raggi et al [13,14] in which small changes in QoL and disability were detected over a three-month follow-up period in samples of patients currently under treatment, although headache frequency was substantially stable.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These positive outcomes were less evident in two studies: the double-blind, randomised placebo-controlled study on levetiracetam in CDH by Beran and Spira [6] and the randomized study on osteopathic manipulative treatment of female patients with migraine by Voigt et al [16], In these reports, however, some changes towards improvement in QoL and in disability were observed. Similar results were found in the two observational studies by Raggi et al [13,14] in which small changes in QoL and disability were detected over a three-month follow-up period in samples of patients currently under treatment, although headache frequency was substantially stable.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies reported short-term longitudinal observations of patients currently under treatment for migraine who were prescribed tailored medications including both acute and prophylactic ones [13,14]. Two studies presented results of non-pharmacological treatments, the first was based on a patient education programme [15] and the second on osteopathic manipulative treatment [16]. Finally, the two trials on b-blockers also included a behavioural management approach in migraine treatment [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…The author claimed a significant improvement in the quality of life parameters as well as a reduction of pain. 17 Another piece of research evaluated the effects of OMT in patients with headaches. Patients who received 8-12 osteopathic sessions showed a significant reduction of pain and frequency of attacks.…”
Section: Introductionmentioning
confidence: 99%
“…However, a query of such bibliogra -tej me to dy w prze wle kłych, prze cią że nio wych oraz na pię cio wych do le gli wo ściach bó lo wych apa ra tu ruchu [20,[25][26][27][28]. Pod czas ana li zy do stęp nych baz biblio gra ficz nych ta kich jak: Pub Med/Me dli ne, Scopus, Co chra ne, Pe dro nie na tra fio no na to miast na arty ku ły na uko we ba da ją ce za sto so wa nie TCK w przecią że nio wych ze spo łach bó lo wych dol ne go od cin ka krę go słu pa. Nie licz ne ba da nia wska zu ją za sto so wanie TCK w ni we lo wa niu na pię cio wych i mi gre nowych bó lów gło wy, a ta kże w le cze niu kol ki po karmo wej u nie mow ląt [29][30][31]. Wo bec te go, trud no powie dzieć co jest przy czy ną prze ciw bó lo we go dzia ła -nia me to dy czasz ko wo -krzy żo wej.…”
Section: Discussionunclassified
“…In ną in ter pre ta cją te go fak tu mo że być dość wy so ka śred -phical databases as PubMed/Medline, Scopus, Cochrane and Pedro did not reveal any papers on the use of CST in low back pain due to overload, with few studies indicating the use of CST in reducing tension headaches and migraine, as well as in treatment of baby colic. [29][30][31]. Thus the mechanism underlying the analgesic effect of craniosacral therapy is un clear.…”
Section: Discussionmentioning
confidence: 99%